1995
DOI: 10.1007/bf00168034
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic neuroma in the pregnant patient

Abstract: We report the case history of a 24-year-old woman with an acoustic neuroma diagnosed during the 24th week of pregnancy. Diagnostic steps and surgical management of this uncommon condition, which represents a therapeutic challenge, are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 3 publications
1
5
0
Order By: Relevance
“…The strategy and planning of the neurosurgical and obstetrical moves may be crucial. Few similar cases have been described previously (9, 25, 31, 32). In the past, prognosis in such cases was very poor (9, 25).…”
Section: Discussionsupporting
confidence: 62%
“…The strategy and planning of the neurosurgical and obstetrical moves may be crucial. Few similar cases have been described previously (9, 25, 31, 32). In the past, prognosis in such cases was very poor (9, 25).…”
Section: Discussionsupporting
confidence: 62%
“…The optimal treatment strategy for both mother and fetus is close observation, followed by tumor resection after delivery. 1,4,5,10,11 The second-best strategy is delivery of the infant (if late enough in the third trimester), immediately followed by tumor resection. 5 Cesarian delivery is the preferred method due to the risk of increased intracranial pressure during phase 2 of vaginal delivery.…”
Section: General Principles Of Managementmentioning
confidence: 99%
“…Intracranial neoplasms rarely present in pregnant women, and diagnosis and management of these tumors during this time poses a significant challenge. 1,2 We describe a patient who presented with a large vestibular schwannoma during her second trimester. We review the literature on similar reported cases, summarize the management strategies according to the stage of pregnancy, and present a treatment algorithm that considers the patient's stage of pregnancy and neurologic status.…”
Section: Introductionmentioning
confidence: 99%
“…7 Other intriguing evidence for a hormonal influence on tumor growth emerges from studies in which preservation of preoperative hearing after VS resection was less likely for premenopausal women than for men or postmenopausal women. 8 It has long been speculated that pregnancy stimulates the growth of VS. Several published reports in the literature describe the infrequent presentation of pregnant patients with VS. 9 VS are statistically more frequent in women, and larger, more vascular tumors are twice as common in women. 10 Since nausea, vomiting, headaches and vertigo are common complaints both during pregnancy and in the presence of brain tumors, though intracranial lesions are rare, it is possible that they may be under-diagnosed or even missed in the pregnant patient until neurological deficits appear.…”
Section: Introductionmentioning
confidence: 95%
“…Other intriguing evidence for a hormonal influence on tumor growth emerges from studies in which preservation of preoperative hearing after VS resection was less likely for premenopausal women than for men or postmenopausal women 8 . It has long been speculated that pregnancy stimulates the growth of VS. Several published reports in the literature describe the infrequent presentation of pregnant patients with VS 9 . VS are statistically more frequent in women, and larger, more vascular tumors are twice as common in women 10 .…”
Section: Introductionmentioning
confidence: 99%